COMPETENCY BASED TRAINING IN THE NURSING HOME SETTING: PROMOTING QUALITY END-OF-LIFE CARE. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - McLaughlin, Dorry; Hasson, Felicity; Foster, Sue; McCorry, Noleen; Kernohan, George; McIlfatrick, Sonja; Watson, Max; Waldron, Mary
Abstract : Background: The importance of good end-of-life care for older people in nursing homes is recognised internationally and competence based training has been highlighted to improve palliative care provision in this care setting. Aim: This aim of this study was to evaluate a three day competency based, Regional Palliative and End-of-Life Care Learning and Development Programme targeted at nursing staff (n=1330) working within nursing homes (n=266) in Northern Ireland. Methods: Both quantitative and qualitative methods were used in two key phases. In Phase 1 participants were asked to complete the Regional Palliative and End-of-Life Care Competency Assessment Tool before and after the training. The content of the programme was mapped to the domains of this tool. In Phase 2, following the programme, seven focus groups with registered nurses (n=29), telephone interviews with managers (n=8) and one focus group, which two managers chose, took place. Results: 619 participants completed the programme and 95.3% (n=590) completed the competency tool before and after the training. Descriptive statistics show participants self-reported a significant increase in core palliative care knowledge and skills across all five competency domains after training. Common themes emerging from focus groups and telephone interviews were: 'Outcomes of attending the programme', programme delivery and issues of access', challenges to palliative care in care homes' and 'enablers to palliative care in the nursing home setting'. Conclusions: This example of training mapped to a competency tool may have relevance given other national and international competency frameworks which exist. Factors relating to attrition have also been identified.